READING MATERIALS IN THE LIFE TODAY ENGLISH BOOK: EFL TEACHERS’ VIEWS - Liani, Ananda Galuh; Komara, Cahya; Asri Yulinar, Niken (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Book is a vital media in EFL Learning process. Life Today book is an English book that becomes one of the primary reading references. However, this book likely has not been widely used by teachers in Indonesia because it is still new. It is interesting to study more on this based on the teachers who have used it. This study examines the reading materials in the English Life Today book of 12 grade in Senior High School level based on EFL Teachers’ view. This research applied mix-method with the use of close-ended and open-ended questionnaires to obtain the opinions of 50 English teachers in Jakarta and some vicinities areas. After gathering the data, the researchers tabulated, analyzed, and interpreted it systematically. The findings showed that 50 EFL teachers dominantly gave positive views towards reading materials in the English Life Today book based on its reading contents aspect, language use, pre-and post-reading, and presentation aspects. The EFL teachers also gave constructive suggestion including the more variation topics need to be added, the extra thesaurus also need to be provided, and the separated reading texts needs to be identified to differentiate low and high students’ level.